Numerical assessment of fixed-ended short-to-intermediate stainless steel starred hot-rolled equal-leg angle sections built-up columns - Sarquis, Fernando Rocha (2024)
Austenitic and duplex stainless steels are chosen for many constructions due to their remarkable corrosion resistance, durability, strength, and aesthetic appeal. However, the current design guidelines of Eurocode 3: Part 1.4, specific to stainless steel structures, often rely on analogies with the behaviour of carbon steel, which may not be suitable due to the specific characteristics of the material, such as its nonlinear behaviour. Additionally, equal-leg angle sections are commonly employed in structural applications, particularly for short-to-intermediate columns exhibiting distinct structural behaviours. The cross-section geometry is characterized by the mid-lines intersecting at a common point (low torsional stiffness), and the centroid is not aligned with the shear centre, which affects these columns’ post-buckling behaviour due to the interaction between displacements around the major and minor inertia axes, directly influencing the element’s ultimate strength. In this context, the use of a starred section, formed by joining two equal-leg angle sections at the corner – aligning the centroid and shear centre, emerges as an efficient solution to mitigate displacement in the major and minor axes during post-buckling behaviour, resulting in a more stable structure. In order to address the gaps related to the use of stainless steel and the application of columns with starred sections, this study conducts a numerical investigation on short-to-intermediate length columns with fixed supports made of austenitic and duplex stainless steel starred sections (both welded and bolted), thus susceptible to torsional buckling. A solid finite element model was developed and validated against experimental results to assess (i) the columns’ elastic buckling behaviour, (ii) elastic post-buckling behaviour equilibrium paths, (iii) initial geometrical imperfection sensitivity, (iv) influence of material mechanical properties of austenitic and duplex stainless steel, and (v) the columns’ ultimate failure load. A parametric analysis was performed through typical compact equal-leg angle cross-sections (i.e., b/t < 20) and selecting column lengths susceptible to torsional buckling failure based on the elastic buckling behaviour. Finally, the numerical ultimate strengths obtained are used to assess whether the design provisions of Eurocode 3: Part 1.4 – column buckling curve “b” – can accurately forecast the ultimate load. Discrepancies between the numerical failure load and the predicted Eurocode buckling ultimate torsional load revealed unduly conservatism. Consequently, two proposed modifications to the European code are suggested, involving a cross-section classification and change of the current buckling curve “b” actually used to assess the design of these structural elements.